IDENTIFIKASI MEKANISME KOPING PADA PASIEN DENGAN KEGANASAN HEMATOLOGI: STUDI DESKRIPTIF - Rani Lisa Inda; Eva Nurhikmah; Sandra Sandra (CV. Naiwa Best Science, 2025)
Hematologic malignancies are becoming a health problem with increasing prevalence globally, posing physical and psychological challenges for patients such as anxiety, depression, and decreased quality of life. Coping mechanisms are important in helping patients adapt. Positive coping can improve quality of life, while negative coping can worsen psychological conditions. This study aims to describe the coping mechanisms of patients with hematologic malignancies at RSUD Arifin Achmad Riau Province. The research method used was descriptive quantitative. The population in this study was patients with hematologic malignancies who underwent treatment at RSUD Arifin Achmad, Riau Province. The sample consisted of 44 respondents who were selected using consecutive sampling. Data were collected using the Brief-COPE questionnaire. The results showed that the average age of respondents was 41.66 years with a standard deviation of 4.92. The majority of respondents were female (54.5%), had a high school education (36.4%), and worked as housewives (43.2%). The most common diagnosis was leukemia (47.7%), with the majority of respondents being married (81.8%). Most respondents (90.9%) had coping mechanisms in the fairly effective. Therefore, we advise health workers to provide education and psychosocial assistance, such as counseling or support groups, to strengthen patient coping. Families are also expected to provide emotional support and be involved in the treatment process